Genome-wide architecture of reproductive isolation in a naturally occurring hybrid zone between Mus musculus musculus and M. m. domesticus - Janoušek, Václav; Wang, Liuyang; Luzynski, Ken; Dufková, Petra; Vyskočilová, Martina M; Nachman, Michael W; Munclinger, Pavel; Macholán, Miloš; Piálek, Jaroslav; Tucker, Priscilla K (Molecular ecology, 2012)
Studies of a hybrid zone between two house mouse subspecies (Mus musculus musculus and M. m. domesticus) along with studies using laboratory crosses reveal a large role for the X chromosome and multiple autosomal regions in reproductive isolation as a consequence of disrupted epistasis in hybrids. One limitation of previous work has been that most of the identified genomic regions have been large. The goal here is to detect and characterize precise genomic regions underlying reproductive isolation. We surveyed 1401 markers evenly spaced across the genome in 679 mice collected from two different transects. Comparisons between transects provide a means for identifying common patterns that likely reflect intrinsic incompatibilities. We used a genomic cline approach to identify patterns that correspond to epistasis. From both transects, we identified contiguous regions on the X chromosome in which markers were inferred to be involved in epistatic interactions. We then searched for autosomal regions showing the same patterns and found they constitute about 5% of autosomal markers. We discovered substantial overlap between these candidate regions underlying reproductive isolation and QTL for hybrid sterility identified in laboratory crosses. Analysis of gene content in these regions suggests a key role for several mechanisms, including the regulation of transcription, sexual conflict and sexual selection operating at both the postmating prezygotic and postzygotic stages of reproductive isolation. Taken together, these results indicate that speciation in two recently diverged (c. 0.5 Ma) house mouse subspecies is complex, involving many genes dispersed throughout the genome and associated with distinct functions.
Keywords: Genetic Speciation; genetická variace; Mating Preference, Animal; jednonukleotidový polymorfismus; reprodukční izolace; chromozom X; vznik druhů (genetika); sexuální výběr u zvířat; X Chromosome; lokus kvantitativního znaku; Animals; Polymorphism, Single Nucleotide; Quantitative Trait Loci; zvířata; Hybridization, Genetic; myši; Epistasis, Genetic; hybridizace genetická; Genetic Variation; Mice; Reproductive Isolation; genetická epistáze